A STUDY ON TYPES OF VOCABULARY TASKS IN EFL TEXTBOOK ENGLISH ON THE SKY 1 - Yanuar Somba; Nihta Liando; Tirza Kumayas (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The purpose of this study is to describe types of vocabulary task in EFL textbooks. This research is a Quantitative research, a type of research where the results are shown in the form of numbers or percentages’ and involves counting and comparisons. In analyzing the data, the researcher used the descriptive analysis included classifying all activities into types of tasks, calculating frequencies, and reporting percentages of each type of task. the study deals with activities in “English on sky 1’’ English Course for Junior High School Students. The textbooks the data consists of 8 chapters and 35 activities with 202 directions. After analyzing the data, the Result show that the data analysis indicates that of 202 directions identified, 86 (or 42.6%) required students to develop their Analysis thinking skill, 50 (or 24.6.%) Knowledge skill, 26 or (12.9%) Comprehension skill, 21(or 10.4%) Application skill, and 14 (or 6.9%) evaluation, 5(2.5%) In addition, of the total data, 202 directions, synthesis and evaluation which are considered as ‘lower-order thinking skills’ (9.4%)   Keywords     : Vocabulary, Bloom Taxonomy, English Textbooks Analysis